A Review of Cellularization Strategies for Tissue Engineering of Whole Organs - Scarritt, Michelle E.; Pashos, Nicholas C.; Bunnell, Bruce A. (Frontiers in Bioengineering and Biotechnology, 2015)
With the advent of whole organ decellularization, extracellular matrix scaffolds suitable for organ engineering were generated from numerous tissues, including the heart, lung, liver, kidney and pancreas, for use as alternatives to traditional organ transplantation. Biomedical researchers now face the challenge of adequately and efficiently recellularizing these organ scaffolds. Herein, an overview of whole organ decellularization and a thorough review of the current literature for whole organ recellularization are presented. The cell types, delivery methods, and bioreactors employed for recellularization are discussed along with commercial and clinical considerations, such as immunogenicity, biocompatibility, and FDA regulation.